The Evaluation of the Patients' Health Status by the Nurses Working in Tehran - Shiva PejmanKhah; Sheida PejmanKhah; Hamid Alavi Majd (Golestan University of Medical Sciences, 2013)
Background and Objective: Nurses should be so determined and competent that, in the dynamic and changing conditions of the patients, they could use their technical skills and professional knowledge to make a rigorous clinical judgment about the patient's health status. Accordingly, a study was conducted to assess the health status of patients and nurses in the hospitals affiliated  with  the social security organization in Tehran, Iran.Material and Methods: This descriptive - analytical study was conducted  on 96 nurses working in medical-surgical and emergency wards of the hospitals affiliated with Social Security Organization in Tehran. The instrument was a questionnaire including two parts of demographic data and 11 questions for assessing nurses' performance. To analyze the data, we useddescriptive and inferential statistics. Results: The mean age is 7.15 ± 32.8 and  75% of the patients are females. Their (53.1%) work of experience is between 73-96 months and their (52.1%) performance is observed poor. There is significant correlation between nurses' performance and variables such as gender, age, marital status, work experience and ward of hospital.Conclusion: Because of low performance of the nurses, it is important for nurses to assess the  health status of patients , the same as physicians using screening forms on the file of patients.